Coronado-era Place-names, I. Marcos de Niza in Sonora, and the Occurrence of Yaqui Names in his Relación. (1st October 2015) - Hartmann, William K.; Harley, Heidi; Fabián, Constantino Martínez
Abstract : Two words used by Marcos de Niza in the first European report on travel north through Sonora (1539) '" Sayota " and " Vacapa "' appear to be traceable to the Hiaki (Yaqui) language. Also, the Coronado expedition's assignment (1540) of the name "Yaquimi" to what is now called the Río Yaqui, in its middle stretch near Onavas, indicates the presence of Hiaki/Yaqui-speakers in that region. These results are used to constrain the likely region of Hiaki/Yaqui-speaking peoples in 1539–42 and also the poorly known movements of Marcos de Niza and the Coronado expedition in Sonora at that time.